2019
DOI: 10.1155/2019/8585276
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNA: Small Molecules, Big Impact in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the major causes of cancer-related deaths worldwide. Tumor microenvironment (TME) contains many cell types including stromal cells, immune cells, and endothelial cells. The TME modulation explains the heterogeneity of response to therapy observed in patients. In this context, exosomes are emerging as major contributors in cancer biology. Indeed, exosomes are implicated in tumor proliferation, angiogenesis, invasion, and premetastatic niche formation. They contain bioactive mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 157 publications
1
33
1
1
Order By: Relevance
“…miRNAs can induce translational inhibition or degradation of its mRNA target, thus constituting a key part of post-transcriptional regulation of mRNA expression. In addition, exosomal miRNA is also closely related to cancer progression 11 . A study has revealed that BMSC-derived exosomal miRNAs in hypoxic conditions facilitate metastatic behaviors of lung cancer cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs can induce translational inhibition or degradation of its mRNA target, thus constituting a key part of post-transcriptional regulation of mRNA expression. In addition, exosomal miRNA is also closely related to cancer progression 11 . A study has revealed that BMSC-derived exosomal miRNAs in hypoxic conditions facilitate metastatic behaviors of lung cancer cells 8 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the aberrant miRNA levels dictated the imbalance of Treg/Th17 cell ratio in epithelial ovarian cancer ( 24 ). The colon cancer cell migration and invasion were mainly ascribed to the aberrant miR-155 and miR-21 levels contained in the exosomes ( 25 ). Consistent with these previous findings, in this study, we identified a novel miR-148b-5p as a critical regulator of tumor immunity environment.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the exosome-derived miRNAs stably circulate in body fluids in a cell-free form and might reflect the miRNA signature of the parental or metastatic tumor [ 109 ]. Thus, secreted exosomes are associated with disease status, such as stage and tumor progression as well as drug resistance [ 88 , 110 , 111 , 112 ]. Therefore, exosomal miRNAs are useful for predicting both strategy of chemotherapy as well as drug resistance.…”
Section: Clinical Application Of Mirnas As Anti-cancer Drug Resistmentioning
confidence: 99%